2016
DOI: 10.1111/efp.12277
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of powdery mildew caused by Podosphaera pannosa on lemon eucalyptus

Abstract: In 2014, powdery mildew was observed on pot-grown lemon eucalyptus (Corymbia citriodora, Myrtaceae) in Korea. Based on morphological data and phylogenetic analysis of anamorph isolates, this fungus was identified as Podosphaera pannosa. This is the first report of powdery mildew caused by P. pannosa on lemon eucalyptus. Our results, which include a detailed morphological description and molecular data analysis, support previous records of P. pannosa on Eucalyptus spp. and thus on taxa outside the Rosaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…These results confirm the hypothesis raised by Silva et al (2001), who previously suggested that the eucalypt powdery mildew pathogen in Brazil was similar to the rose powdery mildew pathogen, P. pannosa, on the basis of morphological analyses of the anamorph and cross-inoculation studies. The results generated in this study also corroborate the results of Cho et al (2016), who reported P. pannosa as the causal agent of powdery mildew on Corymbia citriodora in Korea. This is a significant finding because it now confirms P. pannosa as the causal agent of a very important disease on eucalypt in Brazil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm the hypothesis raised by Silva et al (2001), who previously suggested that the eucalypt powdery mildew pathogen in Brazil was similar to the rose powdery mildew pathogen, P. pannosa, on the basis of morphological analyses of the anamorph and cross-inoculation studies. The results generated in this study also corroborate the results of Cho et al (2016), who reported P. pannosa as the causal agent of powdery mildew on Corymbia citriodora in Korea. This is a significant finding because it now confirms P. pannosa as the causal agent of a very important disease on eucalypt in Brazil.…”
Section: Discussionsupporting
confidence: 91%
“…Lév.] in Italy, United Kingdom, Denmark, Poland, Portugal, Argentina, New Zealand, Australia, South Africa, and Korea (Grasso 1948;Glasscock and Rosser 1958;Spaulding 1961;Gibson 1975;Boesewinkel 1981;Crous et al 1989;Cunnington et al 2003;Delhey et al 2003;Cho et al 2016). Powdery mildew has also been reported on field-grown Corymbia citriodora in Brazil, with leaf deformation and loss of apical dominance observed in young plants (Ferreira 1997).…”
Section: Introductionmentioning
confidence: 99%
“…(Ferreira, 1989). In 2014, in Korea, the first occurrence of powdery mildew caused by Podosphaera pannosa was identified in Corymbia citriodora (Cho et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Podosphaera pannosa is a pathogen with a broad host range, (Braun & Cook, 2012) and Corymbia citriodora (Myrtaceae) (Cho, Park, Lee, Lee, & Shin, 2016). On eucalypt, P. pannosa has been reported in several countries including Argentina, Brazil, Australia, Denmark, Italy, New Zealand, Poland, Portugal, United Kingdom, South Africa and recently South Korea (Cho et al, 2016;Old, Wingfield, & Qing Yuan, 2003).…”
Section: Introductionmentioning
confidence: 99%